Rapid assessment of stream integrity on stream segments in the upper Vardar watershed in Skopje Region - Jovanovska, Daniela; Avukatov, Vasko; Melovski, Ljupčo; Hristovski, Slavčo (Macedonian Journal of Ecology and Environment, 2013)
The paper presents the results of the rapid assessment of stream integrity of stream segments in the upper Vardar watershed in Skopje region, with an emphasis on the Vardar as the biggest and the most important watercourse in Macedonia. The river Vardar is under significant anthropogenic pressure, especially in Skopje and its surroundings. The aim of this study is to evaluate stream segments integrity by estimating the land use impact on adjacent riparian habitats, and the impact that multiscale environmental properties have on subbasin features. The results have principally been derived from field data, combined with satellite images and Corine Land Cover, which have been computer-processed with ArcGIS software and set in a model build up on Watershed Habitat Evaluation and Stream Integrity Protocol (WHEBIP). The upper Vardar basin in Skopje region has been divided into 323 subbasins and 323 stream segments as appropriate; 41 of these have been rated as streams with excellent integrity, 53 as very good, 61 as good, 72 as fair and 96 as poor. The results obtained in this study can contribute towards setting priorities for integrated management and a conservation plan for watersheds and streams in Skopje region, which is crucial since the area is characterized by a high rate of urbanization.